Factors Related to Anemia In Pregnant Women at Hj. Dermawati Nasution Clinic in 2021 - Putri Diah Pemiliana; Ita Kunnisa (Pena Cendekia Insani, 2022)
Background: Anemia is a global health problem that is often found in the community. The World Health Organization (WHO) states that globally the prevalence of pregnant women suffering from anemia is 83.2% and in Southeast Asian countries the prevalence of anemia is 97.8%. Objective: This study aims to determine the relationship between ANC visits, pregnancy spacing and diet with anemia in pregnant women at the Hj Dermawati Nasution clinic in Medan Tembung in 2021. Methods: This type of research used an analytical survey with a cross sectional approach. The study population was 32 respondents and sampling used primary data from interviews and questionnaires as well as secondary data from the MCH book at the Hj Dermawati Nasution clinic in Medan Tembung in 2021. The sample used the Total Population technique, namely the entire population. Chi-square statistical test. Results: The data obtained from the results of statistical tests with Chi-square concluded that there is a relationship between ANC visits and anemia in pregnant women (p = 0.004 < = 0.05), there is a relationship between distance between pregnancy and anemia in pregnant women (p = 0.004 < = 0.05). p = 0.003 < = 0.05), and there is a relationship between food consumption patterns and anemia in pregnant women (p = 0.000 < = 0.05) at the Hj Dermawati Nasution clinic, Medan Tembung 2021. Conclusion: This study has a relationship between visits ANC interval of pregnancy and food consumption patterns with anemia in pregnant women.